Pendampingan Pencatatan Keuangan Dan Penghitungan Harga Pokok Produksi Pada UMKM Di Balikpapan - Rahmayuni, Siti; Pinem, Anwar Arifin; Aulia, Nadya Putri (Abdimas Mandalika, 2025)
This community service aims to assist in financial record-keeping and cost calculation of production to Micro, Small, and Medium Enterprises (MSMEs) in Balikpapan. In this context, effective financial management is crucial for enhancing competitiveness and business sustainability. Through this program, participants will be equipped with the skills to record financial transactions and calculate production costs, essential in determining selling prices and desired profits.The implementation method involves collaboration with local government and is conducted in several stages, starting with data collection of MSMEs, assistance, and evaluation of results. This activity is expected to not only provide practical knowledge and skills but also boost participants' confidence in managing their businesses. Through the evaluation conducted, it is hoped that MSMEs will experience improvements in operations and income after participating in this program. Thus, this community service is expected to contribute positively to the development of MSMEs in Balikpapan and enhance the overall well-being of the community.